2012
DOI: 10.1063/1.4746746
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel auto-combustion synthesis of Li3xMnFe2−xO4 and their characterizations

Abstract: Articles you may be interested inStructural and ambient/sub-ambient temperature magnetic properties of Er-substituted cobalt-ferrites synthesized by sol-gel assisted auto-combustion method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Comparing the coercivity of pure MnFe 2 O 4 (x = 0.0) with the literature value, 11,40 it is observed that the coercivity of the presently investigated sample shows a higher coercivity value. This may be attributed to the fact that the particle size of the presently investigated sample is smaller than the literature reported value.…”
Section: B Magnetic Propertiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Comparing the coercivity of pure MnFe 2 O 4 (x = 0.0) with the literature value, 11,40 it is observed that the coercivity of the presently investigated sample shows a higher coercivity value. This may be attributed to the fact that the particle size of the presently investigated sample is smaller than the literature reported value.…”
Section: B Magnetic Propertiesmentioning
confidence: 82%
“…MnFe 2 O 4 is a ferrimagnet (T N = 560 K) having a spinel structure with two inequivalent sublattices of tetrahedral (A) and octahedral [B] symmetries for the magnetic ions sites. [11][12][13][14] Mn 2+ cation in spinel is at its high spin state. Its five 3d electrons display configurations e 2 t 2 3 and t 2g 3 e g 2 at the tetrahedral and octahedral lattice site, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…High surface to volume ratio improves the properties of nano-sized materials in comparison with their bulk counterparts leading to increase the attention of researchers to explore the materials at nanoscale level. Magnetic oxides, in particular spinel ferrites with nano-size dimension have been comprehensively studied due their distinctive physical properties such as high magnetocrystalline anisotropy, high coercivity, very high chemical and mechanical stability, moderated saturation magnetization, low losses of eddy currents and low conductivity [1][2][3][4][5]. Such unique properties of nano-ferrites make them suitable for various medical and technological applications like waste water treatment [6], treatment for hyperthermia [7], drug delivery carriers [8], magnetic, humidity and biosensors [9][10], microwave devices, high density data storage devices, magnetic recording media, computer memory chips and high frequency devices [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to high chemical stability, considerable magnetic permeability and high electrical resistivity make these materials suitable for several industrial applications. [ 1–5 ] It is well known that intrinsic properties of ferrites like magnetic saturation, Curie temperature, dielectric losses, and d.c. electrical resistivity are greatly influenced by chemical composition, sintering conditions, type of impurity substitution, and site occupancy by metal cations, etc. [ 6–8 ] These unique properties of spinel ferrites make them favorable candidate for variety of technological applications such as magnetic recording media, magnetic drug delivery system, data storage, biosensors, hyperthermia treatment, magnetic refrigeration, etc.…”
Section: Introductionmentioning
confidence: 99%